LANGUAGE LABS: THE LOOP OF THE FEATURES, MATERIALS, AND FUNCTIONS - Levita Dwinaya; Corry Caromawati (Indonesian EFL Journal, 2022)
The implementation of Computer-Assisted Language Learning (CALL) in educational institutions has been projected to be inseparable from the language laboratory, short as lab, for decades. This study investigated the current implementation of CALL in ten universities in Bandung, Indonesia, by mapping the features, CALL materials, and functions of the language labs. The data was collected through observation and interviews. There were four findings of this study. First, there were common CALL materials and distinguished ones among the participating universities. Second, there were three types of language labs found according to their common features. One category is the integrated CALL lab, and the other two categories were considered as the transition from one type kind of lab to another. Third, there were four purposes of language labs: test preparation, skill development, pedagogical knowledge practice, and varied. Fourth, the three aforementioned aspects were found to influence one another. These findings provide information that language laboratories in Bandung to some degree vary. It also suggests that one aspect will determine the others and results in the setup or management of a language laboratory.Keywords: Computer-Assisted Language Learning (CALL); language laboratory; CALL materials; EFL; higher education.Â Â